ANALYSIS OF THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT, EDUCATION AND HUMAN DEVELOPMENT INDEX ON POVERTY RATE IN CIREBON REGENCY IN 2012-2022 - Shelsa Al Risma; Didi Sukardi; Ila Navilah (Cirebon International Journal of Economics and Business, 2024)
Poverty is a complex and multifaceted problem because it is not only related to economic aspects, but also penetrates into social, health, education and political issues. This study aims to determine whether Gross Regional Domestic Product, Education and Human Development Index have an influence on the Poverty Rate in Cirebon Regency. The data used is secondary data in the form of time series sourced from BPS and other sources using multiple linear regression models. The results showed that the Gross Regional Domestic Product and Education variables partially had no significant effect on the poverty rate in Cirebon Regency while the Human Development Index variable partially had a significant negative effect on the poverty rate in Cirebon Regency. And simultaneously, the variables of Gross Regional Domestic Product, Education and Human Development Index have a joint or simultaneous effect on the poverty rate in Cirebon Regency based on the coefficient of determination test which has an effect of 77.5%..